Improvement of the Current System for Atmospheric Air Quality Monitoring in Kyiv According to the EU Requirements - Дворецька, І. В.; Савенець, М. В.; Надточій, Л. М.; Баштаннік, М. П.; Жемера, Н. С. (Київський національний університет імені Тараса Шевченка, 2022)
The paper is dedicated to the problems of the current system for atmospheric air quality monitoring which is operated by the national hydrometeorological service of Ukraine in Kyiv. The problems are discussed in the context of implementing the Directives of the European Parliament and the Council on ambient air quality. The improvement of the current monitoring system needs immediate solutions due to the nonconformity to modern requirements not only in Kyiv, but also on the entire Ukrainian territory. The study makes an attempt to define the main steps of network improvement and the optimization of air pollution measurement network using air pollution data from the archives of the Central Geophysical Observatory, pollutants’ emission, land-use/land cover and meteorological data for 2000-2019. We discuss main EU requirements for monitoring sites’ location, atmospheric air pollution and emission data. The analysis showed the necessity for preliminary urban field measurements before the establishment of monitoring sites. Depending on the wind regime, the new measurement network must take into account the prevailing synoptic processes for future understanding how air pollution is transported towards and outwards the urban area. Land-use/ land cover data derived from the Landsat allowed distinguishing residential areas, industrial zones, main roads, water bodies and green areas which is crucial for the selection of suitable places for monitoring sites. Using mentioned principles and requirements, we propose 15 monitoring sites for the improved air quality network in Kyiv. This number of sites are greater than EU Directives claimed because conclusions were made on theoretical estimations without field measurements. The presented list of the monitoring sites needs additional analysis of spatio-temporal pollutants’ distribution in combination with atmospheric modelling. However, the analysis considers actual residential areas and emission sources in the background of the modern wind regime in Kyiv.

Робота присвячена проблемам діючої мережі спостережень за забрудненням атмосферного повітря національної гідрометеорологічної служби України в місті Києві в контексті імплементації Директив Європейського Парламенту та Ради з охорони якості атмосферного повітря. Питання удосконалення діючої системи спостережень не тільки в місті Києві, але й на всій території України, підлягає негайного вирішення в зв’язку з невідповідністю сучасним вимогам. В роботі проаналізовано діючу мережу спостережень в м. Києві та її відповідність вимогам Директив ЄС та зроблено спробу визначення основних кроків для її удосконалення та оптимізації системи вимірювань забруднення атмосферного повітря.
Удосконалення діючої системи спостережень за якістю атмосферного повітря в м. Києві у відповідності до вимог ЄС
Keywords: мережа спостережень; забруднення атмосфери; директиви ЄС; пункт спостережень; викиди; monitoring network; air pollution; EU Directives; monitoring site; emissions